2021
DOI: 10.1111/cei.13572
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of immunomodulatory M2 macrophages suppresses experimental autoimmune encephalomyelitis in C57BL/6 mice via blockading NF-κB pathway

Abstract: Macrophages play important roles in multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE), and M2 macrophage may have anti-inflammatory effects. In this study, we elucidated the roles of M1 and M2 macrophages in the pathogenesis of EAE and the effects of treatment with M2 macrophages that target certain proinflammatory cytokines and with immunomodulatory preparations that beneficially influence the disease course. We found macrophages increased at the onset of clinical signs in the EAE gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…BAY11‐7082 could also diminish EAN symptoms and delay the onset of EAN by reducing M1 macrophage and proinflammatory cytokine accumulation and increasing M2 macrophage proportion in preventive group. In vitro , BAY11‐7082 inhibited the activity and proliferation of M1 macrophages, which was similar to other results [16]. Overall, these results demonstrated that the NF‐κB signaling pathway may be involved in the pathogenesis of EAN by regulating the polarization of macrophages and inhibiting the expression of inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 89%
“…BAY11‐7082 could also diminish EAN symptoms and delay the onset of EAN by reducing M1 macrophage and proinflammatory cytokine accumulation and increasing M2 macrophage proportion in preventive group. In vitro , BAY11‐7082 inhibited the activity and proliferation of M1 macrophages, which was similar to other results [16]. Overall, these results demonstrated that the NF‐κB signaling pathway may be involved in the pathogenesis of EAN by regulating the polarization of macrophages and inhibiting the expression of inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, this study showed that following immediate administration of MP2 after the occurrence of a motor defect, the Peak phase of disease can be alleviated. Also, in this study, various frequencies of MP2 were transferred prior to the Peak of disease, and eventually, after the third cell injection, the Peak level was alleviated, and the Recovery phase was initiated [11]. Besides, Joanna Mikita et al treated the first dose of MP2 on the third day after EAE Onset.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Xing-Mei Zhang contained the high-quality score [12], and medium quality was detected in 3 remaining papers of Chu et al, Mikita et al, and Tierney et al [11,13,14] (Table 2 and Figure 2).…”
Section: Quality Assessment Of Included Articles For Biasmentioning
confidence: 99%
“…Moreover, while mAbs do not affect the cytokine-producing cells, several of our inhibitors, particularly 6 and 19 , selectively induced cell death in the LPS-activated macrophages, significantly stronger than the reference compound, CAPE. This could be an interesting additional effect of the novel compounds, worthy of being explored in future studies as macrophage infiltrates are especially associated with tissue damage and inflammation in metabolic syndrome [ 57 ], inflammatory brain disorders, and autoimmune diseases [ 57 , 58 ]. In addition, macrophages are implicated in the destabilization of atherosclerotic plaques, leading to acute coronary syndromes and sudden death.…”
Section: Discussionmentioning
confidence: 99%